Use of a Mini-Scleral Lens in Patients with Keratoconus - Semra Akkaya Turhan; Deniz Özarslan Özcan; Ebru Toker (Türk Oftalmoloji Dergisi, 2020)

(untitled)
Objectives:To assess the visual performance of a mini-scleral lens in patients with keratoconus and to evaluate its fit by optical coherence tomography (OCT).Materials and Methods:Twenty-nine eyes of 24 patients with keratoconus were fitted with a mini-scleral lens (Esclera; Mediphacos Inc., Belo Horizonte, Brazil). Diagnostic lenses were used in the initial fitting process. The lens fit was evaluated by the fluorescein pattern and also by anterior segment OCT (RTVue, Optovue Inc., Fremont, CA). Within 30-45 minutes after insertion, the lens fit parameters including central corneal and limbal clearance, and peripheral landing zone alignment were evaluated by OCT. High- and low-contrast visual acuity (VA), subjective performance for comfort and vision (5-point Likert scale), and overall satisfaction with the lens (100 mm visual analog scale [VAS]) were measured before and after lens wear.Results:The mean decimal high-contrast VA (best spectacle-corrected VA: 0.40±0.14 vs VA with the scleral lens: 0.93±0.12, p<0.0001) and low-contrast VA (best spectacle-corrected VA: 0.60±0.24 vs VA with the scleral lens: 1.15±0.18, p<0.0001) significantly improved with lens wear. The mean central corneal clearance was 120.7±24.5 μm. There were no correlations between the keratometric values and the sagittal depth of the scleral lens. The mean number of trial lenses required for ideal fit was 2.2 lenses (range: 1-8). Patients reported high scores for comfort (mean score: 4.69; range: 4-5), vision (mean score: 4.62; range: 3-5) and overall satisfaction with the lens (mean VAS score: 88.1; range: 70-100).Conclusion:The mini-scleral lens provided good high- and low-contrast visual acuity and high patient satisfaction in patients with keratoconus. Anterior segment OCT imaging facilitated the evaluation of the fit.